Relationship Marketing Effectiveness Model for an Indian NBFC - Suar, Prasanta Kumar; Mishra, Sasmita (Indian Journal of Marketing, 2020)
The aim of this empirical article was to develop and validate a model to measure relationship marketing effectiveness in an Indian NBFC context that deals with small road transport operators (SRTOs). Data were collected from 302 truckers by five trained data collectors from different locations of India with the help of a structured interview schedule. Customers, whoever came to the branch office during the study period (January – December 2018) and were willing to participate, were interviewed face to face. After scale validation and outlier elimination, finally 255 responses were analyzed with the help of AMOS 23.0 and SPSS 24.0. Path analysis results revealed that perceived effectiveness of RM directly influenced customer satisfaction, loyalty behavior, and quality of life. Further, customer satisfaction influenced loyalty intention. All the fit indices revealed that the proposed model was a fit model. This revealed that satisfaction could create an intention to repeat purchase and spread word of mouth, but it is the perceived relationship marketing effectiveness that makes customers take another loan or continue with the organization. The findings of the study contribute to the concept of RM effectiveness by measuring its impact on the quality of life of the customers. This study provides new prospectives for the companies doing business in this line to develop unique ways to create value for the customers. Future research can be directed at validating the model in the industry context.